Penerapan Prinsip Tadarruj Dalam Konversi Bank Konvensional Menjadi Bank Syariah - Khomeini, Mohammad Falaq; Saputra, Mohamad Alam; Anam, Khoirul; Aurel, Azi (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2016)
The main principle in the establishment of Islamic banks through the conversion process is to provide ease in setting up Islamic banks. This can be analogized to the process of someone becoming a convert to Islam (muallaf), where all prior backgrounds and sins before embracing Islam are considered erased or forgiven. However, the most crucial aspect of the conversion process is ensuring that no conventional business activities involving gharar (uncertainty) and riba (usury) are conducted by the bank after transitioning into an Islamic bank. This process aligns with the concept of tadarruj (gradualism), where the transformation from a conventional bank to an Islamic bank must be carried out in a planned and sustainable manner. This research aims to analyze the application of the tadarruj principle in the conversion of conventional banks into Islamic banks. This research uses a library research method and is qualitative in nature. The research data is then analyzed descriptively-qualitatively to obtain a comprehensive picture of the issues being studied. The results of this research indicate that implementation of tadarruj will make conventional banks to Islamic banks easier because there is planning, stages and controlled, not spontaneously. Which is in accordance with the meaning of the word, tadarruj itself has the meaning of gradual/stages/slowly. But on the other hand, conversion from Islamic banks to conventional banks is prohibited because there are basic sharia principles that must be upheld. Islamic banks are established with strict sharia principles, including the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling). Changing the status to a conventional bank would be contrary to these principles, as also stated in POJK article 3, that